Possibilidades da psicanálise lacaniana diante da terminalidade: uma reflexão sobre a clínica da urgência - Baroni, Claudia Sofia Ferrão (2011)
This work intends to reflect on the possibilities of a Lacanian psychoanalysis treatment facing terminality at a Psychological Urgency Attendance. The proposed work was a theoretical study drawn from 15 years of Lacanian clinical practice with cancer terminally ill patients. It aims to identify the main Lacanian operators such as unconscious, desire and structure of the subject, which help in the analytical hearing of the story of people living a somatic finitude so they can rebuild the signifying chains that constitute them as a unique subject. To illustrate the possibility of expansion of Lacanian concepts it was used the "vignettes" of clinical cases, resulted from the Lacanian practice of the author. To support this work, at first, it was chosen, along with Freud and Jacques Lacan and their original works, authors that are reference for Lacanian psychoanalysis formation and Lacanian psychoanalysis and others who have the practice in caring for people with cancer and hospitalization. Then it was chosen some authors who are national and international reference in the study of death and terminality, making a description of the phenomenon of death. It arises as critical, the listening to the reason that each subject gives to the illness, since this explanation will assign a subjective sense, allowing the construction of a meaning. The unconscious is timeless and in front of the Real time is replaced by a new dimension for the individual, with the precipitation of the unconscious subject. Narrowing of time can give rise to a demand for giving a meaning to the life lived. What enables the analysis to occur is the handling of transference, in the grounds of ethical and technical procedures and the analyst's desire and for this to occur it is not necessary a perfect setting. The urgency can be seen as an opportunity for a new position of the subject towards his own questions, enabling him to build new outlets for his subjective troubles. We conclude that it up to the psychoanalyst who falls within the emergency clinic to be sustained by concepts of the demands of the attendance that will need to be presented in words, because it refers to a bet on the subject, seeking to modify the emergency situation where the subject is devoid of words, by entering him again in the signifying chain